BEYOND TIKTOK: OPTIMIZING SOCIAL MEDIA PLATFORM FOR ENGLISH LEARNING PURPOSE - Ferdi Arifin (IAIN Syekh Nurjati Cirebon, 2022)
All of Indonesian students take an English subject since elementary school to high school, but less then 50% of the students are not fluent in English. There must be a new way to deliver English materials for students, and one of them is optimizing Tiktok that is a popular social media among them. Tiktok provides many features in its platform for socializing, communicating, and learning. The research aims to elaborate Tiktok as an effective social media for English learning purpose. It is a qualitative method that employs netnography approach. The results shows that many educators have already optimized Tiktok as a medium for English learning. There are several recommendations derived from Tiktok as good tools to catch up students to have feeling joy and find happiness during English learning.